2013 Nepal Enterprise Survey : Country Highlights - World Bank; International Finance Corporation (Washington, DC, 2014)
The chart compares the performance of Nepali firms in 2009 and in 2013 by three performance measures: sales, employment, and labor productivity. Firms are performing at comparable levels compared to four years ago. However, Nepali firms perform slightly better in terms of annual employment growth compared to 2009. The Enterprise Survey covers several topics of the business environment as well as performance measures for each firm. The main highlights from the survey are: the average wait times for obtaining permits and licenses are shorter in Nepal compared to other countries; firms in Nepal report higher rates of female participation; the Nepali private sector considers political instability as the biggest business environment obstacle small firms; firms in Nepal are compensating for the poor electricity infrastructure through the use of generators; and small firms in Nepal require higher collateral values for loans compared to larger firms.